2017
DOI: 10.1590/2359-3997000000203
|View full text |Cite
|
Sign up to set email alerts
|

Importance of abdominal circumference and body mass index values in predicting male hypogonadism – A practical approach

Abstract: Objective: The objective of this study was to correlate the values of abdominal circumference (AC) and body mass index (BMI) with the levels of total testosterone (TT), free testosterone (FT) and sexual hormone binding globulin (SHBG). We aimed to analyze the association between the anthropometric values and variations in the hormonal levels. Subjects and methods: A transversal prospective study was conducted. A total of 159 patients were included in the study. Results: BMI was inversely correlated with TT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Works available in literature primarily describe relationships between indicators based on anthropometric measurements (BMI, WC, WHR) and TT levels in men. Many studies show an inverse correlation between BMI, WHR and WC values and TT concentration, which clearly indicates that excessive fat accumulation, indirectly measured by the above-mentioned anthropometric indicators, is related to hypogonadism [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Works available in literature primarily describe relationships between indicators based on anthropometric measurements (BMI, WC, WHR) and TT levels in men. Many studies show an inverse correlation between BMI, WHR and WC values and TT concentration, which clearly indicates that excessive fat accumulation, indirectly measured by the above-mentioned anthropometric indicators, is related to hypogonadism [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Massachusetts Male Aging Study (MMAS) [16] and the European Male Aging Study (EMAS) [17] performed in large groups of middle-aged and elderly men have shown that BMI and WC are independently associated with decreased values of total testosterone. Jaworski et al, in addition to observing an inverse association of testosterone with BMI and WC, further reported a higher strength of association between abdominal circumference and TT, when compared to the association between BMI and TT [18]. The only study in the literature that determined the relationship of WHt ratio with testosterone showed that the WHt ratio was more strongly correlated with TT than either WC or BMI [19].…”
Section: Discussionmentioning
confidence: 98%
“…However, a longitudinal prospective study reported no correlation between BMI and testosterone levels after adjusting for age. 24 In addition, a bidirectional Mendelian randomization study suggested that BMI had a causal effect on serum testosterone levels in men. 25 Wood et al .…”
Section: Discussionmentioning
confidence: 99%